Impact of social support on college students’ anxiety due to COVID-19 isolation: Mediating roles of perceived risk and resilience in the postpandemic period - He, Tai Bo; Tu, Chia Ching; Bai, Xue (Frontiers in Psychology, 2022)
Because of the transmission and spread of the COVID-19, several universities and colleges in Xi'an, China decided to take quarantine measures and closed their school gates, which increased anxiety among college students. The Perceived Social Support Scale, Perceived Risk of COVID-19 Pandemic Scale, Connor–Davidson resilience scale, and Self-Rating Anxiety Scale were used for measurements. From a questionnaire survey conducted on students in five colleges and universities under quarantine due to the epidemic, 2,251 valid responses were collected for analysis (mean age = 19.60 years, 41.6% women). Social support was discovered to have had a significant negative effect on anxiety. The students’ perceived COVID-19 risk and resilience played significant mediating roles in the relationship between social support and anxiety.